2021
DOI: 10.1002/agr.21704
|View full text |Cite
|
Sign up to set email alerts
|

Perish or prosper: Trade patterns for highly perishable seafood products

Abstract: In recent years trade with highly perishable agricultural products like fresh fish, berries, and cut flowers has increased substantially. The perishability of these products appears to challenge conventional wisdom when it comes to food trade, which emphasizes the importance of large shipments to reduce transportation costs. In this paper, gravity models and several margins of trade are estimated for the trade with fresh salmon, a highly perishable product. The results indicate that increased geographical dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…The marine segments are known to consist of larger enterprises producing mainly salmon, seabass and seabream [44] . The enterprises harvest relatively high volumes of fish that mostly are aimed for supermarket chains on fixed contracts, and have larger capacity to serve different supply chains [8] . Therefore, this segment seems less affected by the crises.…”
Section: Survey Resultsmentioning
confidence: 99%
“…The marine segments are known to consist of larger enterprises producing mainly salmon, seabass and seabream [44] . The enterprises harvest relatively high volumes of fish that mostly are aimed for supermarket chains on fixed contracts, and have larger capacity to serve different supply chains [8] . Therefore, this segment seems less affected by the crises.…”
Section: Survey Resultsmentioning
confidence: 99%
“…However, it limits the degree of coordination that can be obtained between buyers and sellers and prevents relation specific investments (Kvaløy and Tveteras, 2008), suggesting that for some supply chains other transaction mechanisms may be more efficient. Asche et al (2021) indicate that this may be the case for fresh seafood due to its high degree of perishability.…”
Section: Introductionmentioning
confidence: 96%
“…However, there are some observations that assert that a different pattern can be found for the salmon trade. For instance, in their study, Asche et al (2021) conclude that the gravity model of the salmon trade showed different pattern in comparison to storable food commodities. They argue that the distance doesn't have the same magnitude of effect and that economies of scale in transport is not utilized for salmon.…”
Section: Introductionmentioning
confidence: 96%